2015
DOI: 10.1142/9789814675475_0015
|View full text |Cite
|
Sign up to set email alerts
|

Impedance and Component Heating

Abstract: The impedance is a complex function of frequency, which represents, for the plane under consideration (longitudinal, horizontal or vertical), the force integrated over the length of an element, from a "source" to a "test" wave, normalized by their charges. In general, the impedance in a given plane is a nonlinear function of the test and source transverse coordinates, but it is most of the time sufficient to consider only the first few linear terms. Impedances can influence the motion of trailing particles, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Section IV contains the numerical proof for beam stabilization with an rf quadrupole. The study is based on a slow head-tail instability that is observed in the LHC and proven to be Landau damped by means of the magnetic octupoles both experimentally and in simulations [11]. Here, tracking studies show that an rf quadrupole manages to stabilize the beam in a similar manner.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Section IV contains the numerical proof for beam stabilization with an rf quadrupole. The study is based on a slow head-tail instability that is observed in the LHC and proven to be Landau damped by means of the magnetic octupoles both experimentally and in simulations [11]. Here, tracking studies show that an rf quadrupole manages to stabilize the beam in a similar manner.…”
Section: Introductionmentioning
confidence: 92%
“…The numerical validation of the stabilizing effect of an rf quadrupole is based on a horizontal single-bunch instability originally observed experimentally in the LHC at 3.5 TeV during machine commissioning in 2010 [11]. Dedicated studies in the LHC demonstrated that this particular instability is characterized as a slow head-tail mode with an azimuthal mode number m ¼ −1.…”
Section: Numerical Proof Of Conceptmentioning
confidence: 99%
“…It consist of an optimizer that creates and distributes elliptical designs over a number of parallel running tuners used for the frequency adjustment. The optimizer uses a constrained BFGS algorithm 3 to minimize an arbitrary chosen quality function uðxÞ with the special feature that the entries of the Jacobian ∂u=∂x i (with x i as free design variables) are calculated in parallel. Using a five-point differentiation in each variable the parallelization reduces the evaluation by a factor of 10 on an Intel i7 processor of the third generation.…”
Section: A Optimizationmentioning
confidence: 99%
“…The incoherent frequency or tune spread is caused by nonlinearities in the machine. To ensure this mechanism dedicated nonlinear elements, typically octupole magnets, also known as Landau octupoles (LO) are installed in the accelerator [3,4]. However, adiabatic damping and increased beam rigidity reduce their efficiency at higher energies.…”
Section: Introductionmentioning
confidence: 99%
“…According to Refs. [20,21], the incoherent tune shifts δν ≡ ðδν x ; δν y Þ T introduced by the LHC octupoles fed with current I o ¼ þ100 A, with both emittances ε ¼ 2 μm, are as follows:…”
Section: Lhc: Instability Thresholdsmentioning
confidence: 99%